2017
DOI: 10.3390/en10121932
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Heating Element in a Gas-Gas Heater Using an Integrated Analysis Model

Abstract: Gas-gas heaters (GGHs) are used to reheat gases through desulfurization in coal-fired power plants to reduce low-temperature corrosion and white smoke. Wrinkled heating elements are installed inside the GGH to perform effective heat exchange. An optimization study of the heating element shape was conducted to reduce the differential pressure effectively and improve performance. An integrated analysis model was applied. Based on actual operational data, a computational fluid dynamic analysis was conducted on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Several studies have attempted to create efficient CFD simulations of RAPH elements, using techniques such as periodic boundaries and steady flow average turbulence solvers. [6] Other research has found success in physical experiments. Stasiek used a test rig to measure the effect of the corrugation angle, plate pair height, pitch and Reynolds number on pressure drop and heat transfer performance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to create efficient CFD simulations of RAPH elements, using techniques such as periodic boundaries and steady flow average turbulence solvers. [6] Other research has found success in physical experiments. Stasiek used a test rig to measure the effect of the corrugation angle, plate pair height, pitch and Reynolds number on pressure drop and heat transfer performance.…”
Section: Introductionmentioning
confidence: 99%